2018
DOI: 10.5334/jcr.156
|View full text |Cite
|
Sign up to set email alerts
|

Time of Administration of Acute or Chronic Doses of Imipramine Affects its Antidepressant Action in Rats

Abstract: The pathogenesis and therapeutics of depression are linked to the operation of the circadian system. Here, we studied the chronopharmacological action of a tricyclic antidepressant, imipramine. Male adult Wistar–Hannover rats were administered imipramine acutely or chronically in the morning or in the evening. The antidepressant action of imipramine was analyzed using the forced swim test (FST). A single dose of imipramine (30 mg/kg) in the morning, but not in the evening, reduced immobility and increased clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…In the present study, the SNRI venlafaxine showed peak antidepressant activity in the afternoon, whereas the SNRI milnacipran showed potent antidepressant activity in the morning in the FST in Wistar-Hannover rats (Kawai et al 2018a). The tricyclic antidepressant imipramine showed maximal antidepressant activity in the morning in rats (Kawai et al 2018b). In contrast, imipramine and amitriptyline showed maximal antidepressant activity in the evening in C57BL/6 mice (present study) and ICR mice (Ushijima et al 2005), respectively.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In the present study, the SNRI venlafaxine showed peak antidepressant activity in the afternoon, whereas the SNRI milnacipran showed potent antidepressant activity in the morning in the FST in Wistar-Hannover rats (Kawai et al 2018a). The tricyclic antidepressant imipramine showed maximal antidepressant activity in the morning in rats (Kawai et al 2018b). In contrast, imipramine and amitriptyline showed maximal antidepressant activity in the evening in C57BL/6 mice (present study) and ICR mice (Ushijima et al 2005), respectively.…”
Section: Discussioncontrasting
confidence: 44%
“…In animal studies, amitriptyline and fluvoxamine were most effective in the early dark phase (Ushijima et al 2005), whereas nomifensine, milnacipran, and imipramine worked best in the light phase (Borsini et al 1990;Kawai et al 2018aKawai et al , 2018b. A behavioral test suggested that the serotonergic and noradrenergic activities of milnacipran may contribute toward its overall antidepressant activity in the morning and evening, respectively (Kawai et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models show that antidepressants are more effective at specific times of day (e.g. milnacipran, fluoxetine, imipramine, venlafaxine, or bupropion) (Kawai et al, 2018a(Kawai et al, , 2018b(Kawai et al, , 2019. There does not appear to be a common mode of circadian regulation as dosing time dependency is seen with drugs that have different modes of action in serotonergic, noradrenergic, and dopaminergic neurons.…”
Section: Timing Medicine Targeted To the Nervous Systemmentioning
confidence: 99%
“…There does not appear to be a common mode of circadian regulation as dosing time dependency is seen with drugs that have different modes of action in serotonergic, noradrenergic, and dopaminergic neurons. Moreover, drugs show different chrono-pharmacological profiles (Kawai et al, 2018a(Kawai et al, , 2018b(Kawai et al, , 2019. The action of neuropsychiatric drugs (eg, lithium, selective serotonin reuptake inhibitors [SSRIs]) is also affected by polymorphisms in circadian clock genes, chronotype, and cellular circadian rhythms, supporting a general role of circadian biology in neuropsychiatric disorders (Rybakowski et al, 2014;McCarthy et al, 2019).…”
Section: Timing Medicine Targeted To the Nervous Systemmentioning
confidence: 99%
“…Complementarily, pharmacodynamic studies describe the association between drug concentrations and their effects [35]. The role of clock genes on antidepressant targets seem to influence antidepressant efficacy and side effects during the day [36,37].…”
Section: Introductionmentioning
confidence: 99%